Women In Post Revolutionary Egyptian Cinema: Female Centered Film Plots (2011-2018) - M.Kamal, May (AUC Knowledge Fountain, 2019)
This thesis investigates the portrayal of women in post revolutionary Egyptian female centered film plots. Following the increase in the social status of women in Egypt as evidenced in the number of women involved in the governmental decision making positions such as the higher participation of women in the Parliament and at ministerial levels. This study explores the representation of women in contemporary Egyptian film. From the literature review, prominent features of female character existing within patriarchal film culture were identified. These characteristics of male dominated female representation include but are not limited to, the representation of women as social roles rather than independent subjects, concealment of femininity, lack of labor autonomy, and a conflicting mother - daughter relationship. In order to determine whether contemporary film culture is aligned with the social progress made by Egyptian women, the deduced schemes of representations were considered the primary frames that the researcher inspected within the films. This inspection was processed through a qualitative content analysis that inferred the continuous existence of the male domination frames. The content analysis was conducted on eleven female characters that played leading or major supporting roles in the five films identified as having female centered plots and produced between the years 2011 and 2018. The choice of qualitative content analysis was made for the purpose of identifying the encoding of women representation. For the decoding of the depicted frames, this thesis conducted an experimental survey on a small sized voluntary sample of female respondents in order to fill in the literature gap and explore the Egyptian female spectatorship’s perception of the female characters depicted. The questionnaire further aimed to identify the potential connections between the general perception on women representation in Egyptian cinema and their perception on the film Asmaa in specific. The contrast between the results obtained from the content analysis and from the experimental surveys highlighted that representation of women in contemporary Egyptian popular cinema has not evolved in alignment with the attained social progress exhibited in society.